2021
DOI: 10.1097/rnj.0000000000000265
|View full text |Cite
|
Sign up to set email alerts
|

Extrinsic and Behavioral Fall Risk Factors in People With Parkinson’s Disease: An Integrative Review

Abstract: Aim The aim of the study was to explore extrinsic and behavioral risks for falls in older adults with Parkinson’s disease (PD). Background Falls that cause injury and disability in people with PD are common. Understanding the role of extrinsic and behavioral factors is important for fall prevention. Design Integrative literature review with search of CINAHL, MEDLINE, and SCOPUS and ancestry searching was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…35 The complex relationship between fear of falling, balance confidence, and balance performance may also have influenced our results. 32 Because it has been shown that a fall prevention program integrated with an outdoor multisurface terrain has improved balance, gait, and mobility measures in older adults when compared with indoor solid ground 36 and those preliminary outcomes of a feasibility study have shown a reduction of outdoor falls among older adults, 37 future fall prevention trials including people with PD should investigate whether an outdoor multimodal training and the adoption of fall protective behavior 38 would reduce the number of injurious falls in this population.…”
Section: Discussionmentioning
confidence: 99%
“…35 The complex relationship between fear of falling, balance confidence, and balance performance may also have influenced our results. 32 Because it has been shown that a fall prevention program integrated with an outdoor multisurface terrain has improved balance, gait, and mobility measures in older adults when compared with indoor solid ground 36 and those preliminary outcomes of a feasibility study have shown a reduction of outdoor falls among older adults, 37 future fall prevention trials including people with PD should investigate whether an outdoor multimodal training and the adoption of fall protective behavior 38 would reduce the number of injurious falls in this population.…”
Section: Discussionmentioning
confidence: 99%
“…This risk is increased by the fact that FOG often co-occurs with substantial balance problems (Bloem et al, 2004). Kuljeerung and Lach (2021) indicate that nurses should evaluate medication effects and promote fall prevention behaviors while the people with PD perform activities during the on- and off-medication states.…”
Section: Introductionmentioning
confidence: 99%